Dinamika Pembelajaran Pendidikan Agama Kristen Multietnik - Yoel Giban; Ester Sugiarsi (SANCTUM DOMINE: JURNAL TEOLOGI, 2023)
The learning process of education is essentially presented in a multi-ethnic and multicultural context. The presence of Christian Education (CE) within the scope of the school aims to provide enlightenment of thought for multi-ethnic and multicultural students in the dynamics of learning, especially in the learning process of Christian Education. Christian Education is presented as a bridge between ethnicities and cultures so that there are values of tolerance in the interpretation of the Christian Faith. The learning process of Christian Education takes precedence over the principle of humanist education to implement faith in the practice of life, namely, students respect each other and love each other as the Lord Jesus commanded believers. The purpose of this research was to see how the dynamics of multi-ethnic learning at SMA Kristen Wamena. This research was conducted at the Wamena Christian High School Senior High School. The qualitative method used for this research explains the reality of the dynamics of the learning process of multi-ethnic Christian education. The use of qualitative methods in this study is to reveal and understand something behind the phenomenon and gain insight and instil multi-ethnic and multicultural values in Wamena Christian High School students. The research result is that learning in SMA Kristen Wamena is heredity, and the learning process runs effectively and efficiently.